Evaluasi Kebijakan Sanksi Terhadap Pemetikan Bunga Edelweis Di Gunung Lawu Dalam Kerangka Hukum Nasional - Muhammad Raffi Uddin; Achmad Baihaqi (Universitas Islam Negeri Islam Kiai Ageng Muhammad Besari Ponorogo, 2025)
Abstract: The Edelweiss is a rare flora whose sustainability status is threatened, so the government has designated it as a protected plant species through Law Number 32 of 2024 concerning Conservation of Natural Resources and Ecosystems and through the Attachment to the Regulation of the Minister of Environment and Forestry Number P.106/MENLHK/SETJEN/KUM.1/12/2018. This study examines two main focuses, namely: (1) a legal analysis of the practice of picking edelweiss on the slopes of Mount Lawu based on the perspective of National Law; and (2) the application of sanctions against perpetrators of these violations in the National legal system. The study used a qualitative method with a field comparative approach. The results of the study indicate that the act of picking edelweiss without a permit is prohibited and has a clear legal basis. The management of the Mount Lawu conservation area has implemented an effective enforcement mechanism, including social sanctions that can have a deterrent effect on violators. The imposition of sanctions that prioritize humanitarian values, education, and moral awareness is considered more appropriate. This study emphasizes the importance of balanced law enforcement between positive norms, environmental ethics, and sharia values. Keywords: Policy; Prohibition on Picking Edelweiss; National Law Abstrak: Bunga edelweis merupakan flora langka yang status kelestariannya terancam, sehingga pemerintah menetapkannya sebagai jenis tumbuhan yang dilindungi melalui Undang-Undang Nomor 32 Tahun 2024 tentang Konservasi Sumber Daya Alam dan Ekosistem serta melalui Lampiran Peraturan Menteri Lingkungan Hidup dan Kehutanan Nomor P.106/MENLHK/SETJEN/KUM.1/12/2018. Penelitian ini mengkaji dua fokus utama, yaitu: (1) analisis yuridis terhadap praktik pemetikan edelweis di lereng Gunung Lawu berdasarkan perspektif Hukum Nasional; dan (2) penerapan sanksi terhadap pelaku pelanggaran tersebut dalam sistem hukum Nasional. Penelitian menggunakan metode kualitatif dengan pendekatan komparatif lapangan. Hasil kajian menunjukkan bahwa tindakan memetik edelweis tanpa izin merupakan perbuatan terlarang dan telah memiliki dasar hukum yang jelas. Pengelola kawasan konservasi Gunung Lawu telah menerapkan mekanisme penindakan yang efektif, termasuk sanksi sosial yang mampu menimbulkan efek jera bagi pelanggar. pemberian sanksi yang mengutamakan nilai kemanusiaan, edukasi, dan kesadaran moral dinilai lebih sesuai. Penelitian ini menegaskan pentingnya penegakan hukum yang seimbang antara norma positif, etika lingkungan, dan nilai-nilai syariat. Kata Kunci: Kebijakan; Larangan Memetik Edelweis; Hukum Nasional.